(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2025)
The character Kolya Krasotkin in Fyodor Dostoevsky’s “The Brothers Karamazov” appears infrequently, but is strongly connected to the ideological transformations of Russia during the period of transitioning development models after the Peasant Reform of 1861 (Nguyen et al., 2024). In this context, even a child can mature prematurely due to the rapid impact of social realities. Kolya can be seen as a spiritual symbol of the young Russian intelligentsia during this stage of ideological ferment. This period was characterized by a vibrant atmosphere with an interweaving of different, even opposing, intellectual currents; specifically, Western philosophical trends of the 18th-19th centuries, especially French Enlightenment thought, including Voltaire and Diderot. Throughout “The Brothers Karamazov,” Kolya Krasotkin is depicted as an adolescent archetype with an aspiration to reach intellectual maturity, yet still wavering and impulsive in his choice of ideals. This choice lies between scientific materialism, atheistic thought, and religious faith, influenced by Alyosha Karamazov. Through Kolya’s case, Dostoevsky conveys a profound philosophical message about the mood and aspirations of the young Russian generation in their ideological choices during this historical transitional period: they might go astray due to “rationalist illusions” but can also find the light of truth if they learn to reconcile reason with faith. Kolya Krasotkin is often considered a minor character and has not been deeply analyzed. This article aims to contribute to the study of Kolya Krasotkin’s role as a philosophical symbol in the context of contemporary Russia. He is a contradictory figure: both superficial and profound, both upright, benevolent, and altruistic, yet also extreme, embodying a naive voluntarism in his worldview.